Energy Subsidies Reform in Jordan : Welfare Implications of Different Scenarios - Atamanov, Aziz (World Bank, Washington, DC, 2015)
Facing a fiscal crisis, Jordan initiated substantial petroleum subsidy reforms in 2012. The government has also long contemplated how to cut electricity subsidies, which surpass the fiscal burdens imposed by the petroleum subsidies. This paper estimates the impacts of the 2012 petroleum subsidies reform on household welfare and government revenues. It also simulates the distributional and fiscal impacts from ending subsidies in the electricity sector, where the pricing structure is more complex than petroleum prices. The paper looks at the direct and indirect impacts of reform. Moreover, the paper discusses the political economy considerations of reform. While the full removal of petroleum subsidies would have increased poverty, the compensatory cash transfer program the government instituted is estimated to have fully offset the negative impact for the poorer population. The impact of reforms in the electricity sector will depend significantly on the implementation method chosen. A flat increase of tariffs toward cost recovery will put a huge burden on the poorest households. However, a progressive increase in tariffs will generate substantial savings for the government, even with compensatory mechanisms to mitigate the strong negative impact on the vulnerable population. The immediate compensation of the losers from reform appears to be a crucial factor in the successful implementation of reforms in Jordan.